Laser-Induced Highly Stable Conductive Hydrogels for Robust Bioelectronics - Li, Yibo; Zhou, Hao; Yang, Huayong; Xu, Kaichen (Nano-Micro Letters, 2024)
Despite the promising progress in conductive hydrogels made with pure conducting polymer, great challenges remain in the interface adhesion and robustness in long-term monitoring. To address these challenges, Prof. Seung Hwan Ko and Taek-Soo Kim’s team introduced a laser-induced phase separation and adhesion method for fabricating conductive hydrogels consisting of pure poly(3,4-ethylenedioxythiophene):polystyrene sulfonate on polymer substrates. The laser-induced phase separation and adhesion treated conducting polymers can be selectively transformed into conductive hydrogels that exhibit wet conductivities of 101.4 S cm−1 with a spatial resolution down to 5 μm. Moreover, they maintain impedance and charge-storage capacity even after 1 h of sonication. The micropatterned electrode arrays demonstrate their potential in long-term in vivo signal recordings, highlighting their promising role in the field of bioelectronics. Highlights: 1 Stable adhesion of pure poly(3,4-ethylenedioxythiophene):polystyrene sulfonate hydrogel to polymer substrates was successfully achieved via a laser-induced phase separation and adhesion method. 2 The resulting conductive hydrogel exhibits a superior wet electrical conductivity up to 101.4 S cm−1 and a spatial resolution down to 5 μm. 3 Such hydrogels hold great promise in robust bio-interfacing electrodes suitable for long-term high-fidelity signal monitoring.